ASSESSING THE IMPLICATIONS OF INDONESIA’S POTENTIAL ACCESSION TO THE 2019 HAGUE JUDGMENTS CONVENTION - Hidayatullah, Fatah; Chairunniswah Yulindra; Zhafirah Estu Ramadhani (Sriwijaya Crimen and Legal Studies, 2025)
This article analyzes the potential impact of Indonesia’s accession to the 2019 Hague Convention on the Recognition and Enforcement of Foreign Judgments in Civil or Commercial Matters (Hague Judgments Convention). Addressing long-standing uncertainty stemming from Article 436 of the Reglement op de Rechtsvordering (RV), the study evaluates three key dimensions: legal certainty, investor confidence, and the implications for state sovereignty. Using a normative and comparative legal approach, the research finds that Indonesia’s current framework, requiring a full fresh lawsuit to enforce foreign judgments, creates high transaction costs, inconsistent judicial outcomes, and diminished trust from foreign investors. The Hague Convention offers a predictable, efficient, and standardized multilateral system that can significantly strengthen Indonesia’s cross-border enforcement regime. Accession would enhance legal reliability and improve the investment climate, provided that Indonesia undertakes legislative harmonization, strengthens judicial and institutional capacity, and maintains adequate safeguards through ordre public and sovereign-immunity protections. The article concludes that Indonesia should pursue accession through a phased and carefully designed approach to balance international judicial cooperation with the preservation of national sovereignty.